Operational Implementation of a Surge Forecast System in the Miraflores and Callao Bays in Lima Peru - Ramos, Carmela (2018)
The Directorate of Hydrography and Navigation (DHN) from Peruvian Navy has implemented a coastal wave forecasting system at the principal bays from Peruvian coast for the purpose to provide early warnings due the extreme wave conditions, that allows to DHN order the close of the main ports for the safety of fishermen and ships. The model used was Delft3D-WAVE, which was used on a stationary basis and run daily in an operational manner. To corroborate the results obtained, it was validated with in situ measurements for approximately 1 year, obtaining a correlation coefficient of 0.62 in the wave height and 0.55 in the wave direction, between the measured and modeled. The results are available on the DHN website.